Outcomes in patients with glenoid labral lesions: a cohort study. Issue 1 (21st February 2017) - Zughaib, Marc; Robbins, Christopher B; Miller, Bruce S; Gagnier, Joel J
Abstract : Background/aim: For patients presenting with glenoid labral pathologies, there is little information on how operative interventions affect long-term outcomes and health-related quality of life (HRQoL). This study evaluated outcomes in operative and non-operative patients presenting with labral tears versus labral degenerations. Methods: Participants completed a pain Visual Analogue Scale (VAS), the Veterans RAND 12-item Health Survey, Western Ontario Rotator Cuff Index, American Shoulder and Elbow Surgeons instrument, Scapular Assistance Test (SAT), Shoulder Activity Level, and Single Assessment Numeric Evaluation at baseline and at 6-month, 12-month and 2-year follow-ups. χ 2 and Student's t-test were used to test the differences between categorical and continuous variables. Analysis of variance investigated the differences between groups, and linear regression analyses explored the relationship of baseline characteristics with outcome scores. Results: After 2 years, the operative cohort (n=68) significantly improved in all measures. The non-operative cohort (n=55) showed significant improvements in all scores except the mental component summary (MCS) and pain VAS. Labral tear patients (n=52) within the operative group (n=28) significantly improved in all measures except MCS. Non-operative labral tear patients (n=24) indicated significant improvements in all measures except MCS, VAS and SAT. Labral degeneration patients (n=71) within the operative group (n=27) significantly improved in all measures except MCS and SAT. Non-operative labral degeneration patients (n=44) indicated significant improvements in all measures except the physical component summary, MCS, VAS and SAT. Conclusion: Patients who were surgically treated for labral tears or degenerations had significantly improved outcomes and HRQoL scores after 2 years compared with the non-operative cohort.